2017
DOI: 10.2147/ijn.s141032
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide and reduced graphene oxide induced neural pheochromocytoma-derived PC12 cell lines apoptosis and cell cycle alterations via the ERK signaling pathways

Abstract: Given the novel applications of graphene materials in biomedical and electronics industry, the health hazards of these particles have attracted extensive worldwide attention. Although many studies have been performed on graphene material-induced toxic effects, toxicological data for the effect of graphene materials on the nervous system are lacking. In this study, we focused on the biological effects of graphene oxide (GO) and reduced graphene oxide (rGO) materials on PC12 cells, a type of traditional neural c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 41 publications
7
55
0
Order By: Relevance
“…PC12 cell lines, derived from rat adrenal medulla pheochromocytoma, can secrete catecholamine transmitters and have sympathetic neuron characteristics, so they have been widely used in vitro to study of neuron injury mechanism [29,30]. Studies have found that severe cerebral hypoxic I/R injury can induce autophagic death of neurons [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…PC12 cell lines, derived from rat adrenal medulla pheochromocytoma, can secrete catecholamine transmitters and have sympathetic neuron characteristics, so they have been widely used in vitro to study of neuron injury mechanism [29,30]. Studies have found that severe cerebral hypoxic I/R injury can induce autophagic death of neurons [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…A similar situation could arise for graphene, the 2D layered nanomaterial, which can also be expected to cause mechanical damage to cell membranes via flat and sharp edges [13,14]. Many studies are focused on graphene oxide (GO), which is described as a promising nanomaterial in nanomedicine despite the fact, that many reports point to its potential cytotoxicity [15][16][17][18][19][20][21][22][23][24][25]. However, there are limited data on biological effects of other derivatives such as GP and graphene sheets to which humans are exposed during development, processing or manufacturing [26,27].…”
Section: Introductionmentioning
confidence: 90%
“…In particular, the exposition to graphene seemed to increase the mitochondrial membrane permeability, provoking the release of apoptosis-inducing factor. Li et al have demonstrated that the intrinsic apoptosis pathway (mitochondrial-mediated) represented the main death mechanism triggered by pristine G [ 76 ]. In particular, the mitochondrial outer membrane depolarization after graphene exposition occurred in a time-dependent manner and resulted in the increment of expression levels of apoptotic effector enzyme, such as caspase-3.…”
Section: Intracellular Molecular Pathways Activated By Functional mentioning
confidence: 99%